2012
DOI: 10.1039/c2an35950b
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of Coulombic interaction in the oriented-attachment growth of colloidal nanorods

Abstract: An analytical expression of Coulomb interaction between a sphere and a cylindrical rod was derived. Along with a recently reported van der Waals interaction expression, the derived Coulomb interaction expression, for the first time, allows one to quantitatively evaluate the activation energy in the oriented attachment growth of colloidal nanorods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 23 publications
(26 reference statements)
1
30
0
Order By: Relevance
“…To study the OA mechanism, a portion of such work has been done by constructing analytical models. 77 The theoretical construction of 1D OA nanostructures largely facilitates the understanding of the kinetic process of the OA growth. It was assumed that spherical NPs are attached to the two sides of a cylindrical NR and then grow into 1D OA NCs.…”
Section: A Model For Growing Oa Nr: Roles Of Vdw and CImentioning
confidence: 99%
“…To study the OA mechanism, a portion of such work has been done by constructing analytical models. 77 The theoretical construction of 1D OA nanostructures largely facilitates the understanding of the kinetic process of the OA growth. It was assumed that spherical NPs are attached to the two sides of a cylindrical NR and then grow into 1D OA NCs.…”
Section: A Model For Growing Oa Nr: Roles Of Vdw and CImentioning
confidence: 99%
“…4, is consistent with the authors' earlier reports, which indicated that the OA growth of thicker nanorods experiences larger CI compared with the OA growth of thinner nanorods. 14,15 The CI versus AR plots with a xed outer radius are shown in Fig. S1; † these plots are comparable to those in Fig.…”
mentioning
confidence: 74%
“…It imply that the contribution of vdW to ln(GS 1 ) could be considered identical in each solvent. Therefore, CI should directly determine the distinction in growth rate of Te nanochains in different solvents, which was described by Coulomb’s law in equation (4)31:…”
Section: Resultsmentioning
confidence: 99%